Effect of Differently Fed Farmed Gilthead Sea Bream Consumption on Platelet Aggregation and Circulating Haemostatic Markers among Apparently Healthy Adults: A Double-Blind Randomized Crossover Trial - Ntzouvani, Agathi (Nutrients, 2021)
Fish consumption beneficially affects coagulation markers. Few dietary intervention studies have investigated differently fed farmed fish against these cardio-metabolic risk factors in humans. This double-blind randomized crossover trial evaluated differently fed farmed gilthead sea bream consumption against platelet aggregation and circulating haemostatic markers among apparently healthy adults. Subjects aged 30–65 years, with a body mass index 24.0–31.0 kg/m(2), consuming less than 150 g cooked fish per week, were recruited in Attica, Greece. Participants were randomized (n = 38, 1:1) to one of two sequences; consumption of fish fed with fish oil diet (conventional fish, CF)/fish fed with olive pomace-enriched diet (enriched fish, EF) versus EF/CF. The primary outcomes were ex vivo human platelet aggregation and circulating plasminogen activator inhibitor-1 (PAI-1) and P-selectin (sP-selectin) concentrations. EF consumption had no significant effect on platelet sensitivity or haemostatic markers compared to CF. Platelet sensitivity to platelet-activating factor (PAF) decreased after CF consumption during the second period (p < 0.01). Plasma PAI-1 and sP-selectin concentrations increased after CF consumption during both periods (p < 0.01 for both). Based on current findings, consumption of enriched farmed gilthead sea bream had no greater effect on coagulation markers in adults compared to the conventionally fed fish.